Rapid purification of glycerol by-product from biodiesel production through combined process of microwave assisted acidification and adsorption via chitosan immobilized with yeast - Saifuddin N.; Refal H.; Kumaran P. (Maxwell Science Publications, 2023)
Biodiesel is a proven alternative to the petroleum diesel fuel. During biodiesel production, glycerol is produced as a by-product. This by-product consist of impureties such as soap, salts, sodium catalyst and so on. Traditionally, two of the most conventional techniques that is applied to glycerol purification are distillation and ion-exchange. These techniques are, however, still expensive to generate pure glycerol. Recently, several alternative "combination" treatment procedures have been used. These treatment has several advantages over others methods such as producing large amounts of glycerol-rich layer that requires simple treatments and not causing any high operational cost. In this study, the combination treatment process have been used in order to reach high glycerol content. Basically, these stages starts with using microwave assisted acidification process and the next process utilizing a bioadsorbent synthesized from dead yeast cells immobilized on chitosan. The final yield of glycerol was about 93.1-94.2% (w/w).